Генетичний інструментарій для конструювання штамів Actinoplanes teichomyceticus із підвищеним рівнем продукції тейкопланіну - Горбаль, Л.О.; Ющук, О.С.; Забуранний, Н.; Кобилянський, А.М.; Осташ, Б.О.; Марінеллі, Ф.; Лужецький, А.М.; Федоренко, В.О. (Фактори експериментальної еволюції організмів, 2014)
Aims. Random mutagenesis and selection were extensively applied to teicoplanin producers, while the gene engineering methods were not used, because of the paucity of genetic tools for A. teichomyceticus. Methods. A set of microbiological, biochemical and genetic methods were used in the study. Results. We worked out an effective method of transfer of integrative and replicative vectors in A. teichomyceticus by means of conjugation. Successful adaptation of the gusA reporter for the use in this strain let us to estimate the strength of different heterologous promoters that might be used for gene expressions in it. Several strains with in average 30–40 times increased level of teicoplanin production in comparison to the wild type were obtained. Conclusions. Based on the obtained results we proposed a new approach for the improvement of teicoplanin production.